2017
DOI: 10.3390/molecules22050685
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Anti-Leishmania (Leishmania) infantum Activity of Some Natural Sesquiterpene Lactones

Abstract: Leishmaniases are neglected infectious diseases caused by parasites of the ‘protozoan’ genus Leishmania. Depending on the parasite species, different clinical forms are known as cutaneous, muco-cutaneous, and the visceral leishmaniasis (VL). VL is particularly fatal and the therapy presents limitations. In the search for new anti-leishmanial hit compounds, seven natural sesquiterpene lactones were evaluated against promastigotes and intracellular amastigotes of Leishmania (Leishmania) infantum, a pathogen caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…The Leishmania plasma membrane regulates the passage of nutrients, and the homeostasis, to maintain viability. SYTOX dye is a nucleic acid stain which combines with DNA, increasing the fluorescence up to 500-fold, which is observed as a green color [19,39,51].…”
Section: Resultsmentioning
confidence: 99%
“…The Leishmania plasma membrane regulates the passage of nutrients, and the homeostasis, to maintain viability. SYTOX dye is a nucleic acid stain which combines with DNA, increasing the fluorescence up to 500-fold, which is observed as a green color [19,39,51].…”
Section: Resultsmentioning
confidence: 99%
“…Based on a previous report about the in vitro and in vivo trypanocidal activity of deoxymikanolide, this compound was selected to carry out a biochemical characterization of its mechanism of action. Even though the presence of an α-β unsaturated lactone moiety is a common structural feature among STLs to which most of their biological activities are attributed, different antiprotozoal mechanisms of action have been described for them (Sülsen et al, 2010;Sülsen et al, 2016;Wulsten et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It will also be of interest to investigate whether the total extract present in the tincture is superior in activity to isolated STL, i.e., helenalin and 11α,13-dihydrohelenalin esters. These compounds are known to possess antileishmanial activity [ 2 , 3 , 4 ] but it is quite likely that their proven anti-inflammatory activity [ 5 , 6 , 7 ] also contributes to the curative effects observed in the present CL model.…”
Section: Discussionmentioning
confidence: 99%
“…One of the preparations tested in this work was a commercial Arnica tincture which showed high activity against Trypanosoma brucei but also considerable growth inhibitory activity on Leishmania donovani , one of the pathogens causing visceral Leishmaniasis. In previous studies, considerable in vitro activity against protozoan parasites had been reported for single consitutents of Arnica, namely, sesquiterpene lactones (STLs) of the helenalin type [ 2 , 3 , 4 ]. Arnica tincture and other preparations from the same plant material are commonly used as safe and efficacious topical treatment for inflammatory conditions of the skin, joints or muscles [ 5 ] which has been mainly attributed to its STLs and their inhibitory activity on inflammatory transcription factor NF-κB [ 6 ].…”
Section: Introductionmentioning
confidence: 99%